2001
DOI: 10.1002/1521-3765(20010401)7:7<1468::aid-chem1468>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dioxygen by a Dimanganese Unit Bonded Inside a Cavity Provided by a Pyrrole-Based Dinucleating Ligand

Abstract: A novel class of dinucleating ligands has been introduced into manganese chemistry to study the reactivity of this metal towards dioxygen under strictly controlled conditions. Such N4 ligands combine some of the major peculiarities of tetradentate Schiff bases and the porphyrin skeleton. They are derived from the condensation between 2-pyrrolaldehyde and ethylenediamine or o-phenylenediamine, leading to pyrenH2 (LH2, 1), pyrophenH2 (L'H2, 2) and Me2pyrophenH2, (L"H2, 3), respectively. Their metallation with [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…Bis-bidentate Schiff base ligands have attracted signi®cant interest as building blocks in metallo-supramolecular chemistry, especially in the synthesis of helicates (see, for example, Kruger et al, 2001;Yoshida & Ichikawa, 1997;Yoshida et al, 2000;Franceschi et al, 2001;Albrecht, 2001). The title compound, (I), has been shown to form helicate supramolecular complexes of the form [M 2 L 2 ] with transition metals (Yoshida & Ichikawa, 1997;Yoshida et al, 2000;Kruger et al, 2001).…”
Section: Commentmentioning
confidence: 99%
“…Bis-bidentate Schiff base ligands have attracted signi®cant interest as building blocks in metallo-supramolecular chemistry, especially in the synthesis of helicates (see, for example, Kruger et al, 2001;Yoshida & Ichikawa, 1997;Yoshida et al, 2000;Franceschi et al, 2001;Albrecht, 2001). The title compound, (I), has been shown to form helicate supramolecular complexes of the form [M 2 L 2 ] with transition metals (Yoshida & Ichikawa, 1997;Yoshida et al, 2000;Kruger et al, 2001).…”
Section: Commentmentioning
confidence: 99%
“…[10][11][12] Despite the ongoing researches into helical structures, few examples exist of neutral compounds that adopt helical structures. [13][14][15][16] Most recently, we demonstrated that pyrrol-2-yl Schiff base ligands serve as ideal building blocks for supramolecular architectures. By variation of the spacers between two pyrrolimine units or the substituents on the pyrrole ring, multidimensional network polymers, dinuclear dimeric helicates, and trinuclear trimeric triangle and tetranuclear tetrameric square complexes were generated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, compound 2 represents the third example as indicated by the Cambridge structural database. Scheme 3 depicts the magnesium compound 2 and the previously reported dinuclear copper (4) [19] and manganese (5) [18] complexes supported by the pyrrolylaldiminate ligands (L 02À ) that contain a proton rather than a t-butyl group at the 5-position. Similar to those observed in 4 and 5, complex 2 possesses a crystallographically D 2 symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguing chemistry evolved from metal complexes containing these ligands has emerged extensively. In comparison, chemistry involving dianionic tetradentate pyrrolylaldiminate ligands remains relatively undeveloped [17][18][19][20][21][22][23][24]. These compounds can be regarded as a tetraaza analogue of ubiquitous salen ligands or an acyclic variation of porphyrin derivatives.…”
Section: Introductionmentioning
confidence: 99%